THE FUTURE OF VILLAGE DEVELOPMENT IN THE HANDS OF NEW LEADERS - Septimawan Sutopo, Dhanny (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
In this article, we explore the future vision of village development on the transition of power. How is the concept of "developing rural areas" in the hands of the new leader. This concept is important for developing close relationships between villages and cities, as well as between adjacent villages. By adopting this paradigm shift, the hope is that villages will no longer only be objects of development, but become subjects of independent and competitive development. This means that villages are expected to take an active role in managing their own potential and local wisdom, as well as being an example for other villages in Indonesia in achieving the nation's ideals.